Window Management for Energy Conservation - Marie Hammer (EDIS)
Windows can provide light, ventilation and an enjoyable view. However, they also can make heating and cooling your home more difficult. On a hot day, more energy will come through just one square foot of clear glass than through an entire insulated wall. Between 20 to 50 percent of the total energy loss in a well-insulated structure occurs through and around the windows and doors. This document is FCS 3091, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: February 2003. First published: January 1988. Reviewed: February 2003.